The Connection Between Your Employees and Customers - K. R., Subramanian (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
As a business, you strive for acquiring and retaining happy customers. However, many businesses do not realize that the process starts with their employees and their job satisfaction with the company. This is one of the most undervalued aspects of developing a durable customer base. The employees want to feel the same way as their customers in their relationship with the company as everyone wants to feel appreciated. One of the negative impacts of modern technology is that many goods and services are turned into commodities. The quality of the service your employees provide is of paramount importance and this happens when  employees are fully engaged. Connected employees are the employees who provide great customer service and a unique experience. Such cumulative experiences have progressively become the predominant motivation for customers to buy. Customers need to receive excellent products and services in order to spend their hard earned bucks. Of course yes, it is employees who will provide them this exceptional product or service. If the employees are miserable in their jobs this affects morale, innovation, and customer relationships and which does not translate into a great product and/or service. This is the connection between employees and customers